Nutrient Digestibility and Performances of Frisian Holstein Calves Fed with Pennisetum purpureum and Inoculated with Buffalo’s Rumen Bacteria - I Prihantoro; D Evvyernie; . Suryani; L Abdullah; T Toharmat (Faculty of Animal Science, Bogor Agricultural University, 2014)
Buffalo’s rumen bacteria (BRB) are potential in digesting fiber feed. BRB already adapted well with low quality forages and agricultural byproducts. The aim of this study was to determine the effect of buffalo’s rumen bacteria (BRB) consortium inoculated into preweaning Frisian Holstein calves on nutrient digestibility, physiological status, mineral uptake, and blood profile. This study used 14 isolates of bacteria isolated from rumen fluid of four local buffalos. The research units consisted of seven Frisian Holstein calves at two weeks old with the average body weight of 43.6±4.5 kg. Calves were inoculated with 20 mL of buffalo’s rumen bacteria isolates [4.56 x 109 cfu/mL] every morning for 10 weeks. The calves were divided into two groups i.e., three calves received bacterial inoculation and four calves without any inoculation. The variables which were analyzed in the preweaning and weaning period were feed intake, digestibility, average daily gain (ADG), feed conversion ratio (FCR), rumen fermentation characteristics, body weight, physiological status, blood profile, and mineral status. Data were analyzed statistically using t-test. The results showed that inoculation of buffalo’s rumen bacteria into Frisian Holstein calves effectively increased feed intake, characteristics of leukocytes and neutrophils, and cobalt (Co) uptake during the weaning period. Inoculation of rumen bacteria improved rumen pH during preweaning and weaning periods. Inoculation of rumen bacteria also had no negative effects on digestibility, feed conversion (FCR), average daily gain (ADG), and physiological status.Key words: buffalo rumen bacteria, digestibility, physiological status, blood profile, Pennisetum purpureum